PSYCHOLOGICAL COSTS OF ACADEMIC SUCCESS: EXAMINING THE IMPACT OF SHADOW EDUCATION ON CHILDREN'S MENTAL HEALTH - Kumar, Sachin Kumar; Pandita, Poonam; Singh, Kiran (International Journal of Research -GRANTHAALAYAH, 2025)
Shadow education, referring to the supplemental, private tutoring provided outside the formal school system has become a global phenomenon. While it aims to improve academic performance, its impact on children’s mental health has raised significant concerns. This paper examines the psychological effects of shadow education on children, exploring issues such as stress, anxiety, pressure to perform, and reduced leisure time. Drawing upon a range of international studies, the paper analyzes the mechanisms through which shadow education contributes to mental health challenges, highlighting the paradox between academic achievement and emotional wellbeing. It also discusses potential interventions to reduce the negative consequences of shadow education, emphasizing the importance of a harmonious blend of learning strategies.